Understanding Investment Motivation in the Young Generation Using Self-Determination Theory - Ilma Wulansari Hasdiansa; Sitti Hasbiah (Fundamental and Applied Management Journal, 2024)
This study aims to analyze the investment motivation of students using the Self-Determination Theory (SDT) framework. SDT emphasizes three basic psychological needs that influence motivation: competence, relatedness, and autonomy. Data were collected through a survey involving students from various disciplines at Universitas Negeri Makassar (UNM). The findings reveal that fulfilling the need for competence through investment training programs and seminars, fostering relatedness through investment communities and discussion groups, and supporting autonomy in investment decision-making significantly enhance students' investment motivation. The conclusion of this study highlights the importance of institutional support in the form of education, community building, and the provision of investment platforms that empower students to make independent decisions. These findings have practical implications for universities and other educational institutions, suggesting the need for effective strategies to boost financial literacy and encourage investment participation among students. By addressing these psychological needs, educational institutions can play a pivotal role in shaping the investment behaviors of the young generation.